The Effect of Paramilitary Protest Policing on Protestors' Trust in the Police: The Case of the "Occupy Israel" Movement. Issue 3 (September 2017) - Perry, Gali; Jonathan‐Zamir, Tal; Weisburd, David
Abstract : The use of paramilitary methods in civil policing tasks has become common in Western police agencies. Despite propositions that such methods should undermine the relationship between the police and the public, the effect of paramilitary policing on public trust in the police has not been empirically tested. In the present study, we examine this question in the context of protest policing, which has become a major concern for Western police agencies. Using a survey of 470 protesters who participated in "Occupy" protest events in Israel in 2012, we find that the perceived use of paramilitary methods has an independent and negative effect on trust, stronger than that of police effectiveness and the "neutrality" component of procedural justice. In‐depth interviews suggest that the significance of paramilitarism may be the result of a sense of alienation and criminalization it elicits among protesters who generally perceive themselves as law‐abiding citizens.